Peran Stakeholders Dalam Meningkatkan Mutu Pendidikan Islam di MTs Barokatul Qodiri Kecamatan Air Kumbang Kabupaten Banyuasin - Firda Fadila Ghassani; Lasni Sutri; Saipul Annur; Asri Karolina (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the role of stakeholders in improving the quality of Islamic education at MTs Barokatul Qodiri, Air Kumbang District, Banyuasin Regency. Improving the quality of education is not only determined by internal school factors, but also the involvement of the madrasah principal, teachers, parents, the community, and the government. This study uses a qualitative approach with field research through observation, interviews, and documentation. The results show that stakeholders play a significant role in improving the quality of educational input, process, output, and outcome. The madrasah principal plays a role in program management, teachers in quality learning, parents in support and motivation for learning, and the community in  social support for the madrasah.Synergy between stakeholders can create a conducive educational environment and support the realization of quality Islamic education